The Effectiveness Of Music Therapy To Reduce Anxiety In Patients With Gastric Acid At Clinic - Ibnu, Alamin; Noviekayati , IGAA; Evitasanti, Dyan (Kirana Publisher (KNPub), 2025)
This study aims to examine the effectiveness of music therapy in reducing anxiety levels in patients with acid reflux and to determine whether there are differences in anxiety reduction based on the Big Five personality traits. The subjects of the study consisted of 10 patients who met the inclusion criteria after undergoing a screening process involving medical records, anxiety assessment using the HARS scale, and personality evaluation using the Big Five personality scale. Music therapy was administered as an intervention to reduce anxiety in these patients. Data analysis was performed using the Wilcoxon Signed Ranks Test to compare anxiety levels before and after the intervention, and the Kruskal-Wallis Test to examine differences in anxiety reduction among the various personality groups. The results showed that music therapy was effective in reducing anxiety in patients with acid reflux. The Wilcoxon test indicated a significant reduction in anxiety levels, with the average anxiety score before the intervention being 30.50, and after the intervention, it decreased to 21.90. This demonstrates that music therapy can significantly reduce anxiety in acid reflux patients. Meanwhile, the Kruskal-Wallis Test revealed no significant difference in anxiety reduction across different personality traits, with a p-value of 0.188 (p > 0.05). Therefore, it can be concluded that while music therapy is effective in reducing anxiety in acid reflux patients, personality traits do not influence the response to this intervention.